2017
DOI: 10.1111/ane.12807
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital pathways of occipital stroke patients with mainly visual symptoms

Abstract: Occipital stroke patients with visual symptoms contact health care late, are inadequately recognized, and present with complex prehospital pathways. Consequently, they are often ineligible for IV thrombolysis. This presents a missed opportunity for preventing permanent visual field defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
3
14
1
Order By: Relevance
“…With perimetry, the frequency of detected VFD in our study was higher at admittance, 79%. Our numbers are in accordance with a large prospective multicenter trial where VFD was found in 52% of a general stroke population, while 86% VFD was reported among occipital stroke patients with mainly visual symptoms admitted to an emergency department at a university hospital in Finland …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…With perimetry, the frequency of detected VFD in our study was higher at admittance, 79%. Our numbers are in accordance with a large prospective multicenter trial where VFD was found in 52% of a general stroke population, while 86% VFD was reported among occipital stroke patients with mainly visual symptoms admitted to an emergency department at a university hospital in Finland …”
Section: Discussionsupporting
confidence: 91%
“…The mean age of the patients was about 70 years, two thirds were men, and hypertension (52%) and smoking (40%) were the most frequent risk factors. The demographics were similar to those presented in the recent study of occipital stroke in Finland, yet the frequency of hypertension, hyperlipidemia, and diabetes was lower in our population . However, the rate of smoking in our patients was substantially higher than the 18% found in the general stroke population in Norway…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This period should preferably be less than three hours (14)(15)(16). However, according to the results of a study by Raty et al, only 5.6% of the patients were referred to the clinics at the desired time (17). In Iran, according to study by Ghiasian et al, the mean delay time was 7.4 hours (18).…”
Section: Introductionmentioning
confidence: 99%